Secular and Cyclical Responses of U.S. Trade to Income: An Evaluation of Traditional Models - Haynes, Stephen E.; Stone, Joe A. (The Review of Economics and Statistics, 1983)
Stephen E. Haynes, Joe A. Stone, Secular and Cyclical Responses of U.S. Trade to Income: An Evaluation of Traditional Models, The Review of Economics and Statistics, Vol. 65, No. 1 (Feb., 1983), pp. 87-95